Application of Electrical Resistance Tomography (ERT) in Resolving Hydrological Problems of a Semi Arid Hard Rock Terrain of Southern India - Rolland Andrade (Science and Technology: Developments and Applications Vol. 4, 2025)
Electrical resistivity is a measure of how strongly a material opposes the flow of electric current. The basic concept of Electrical Resistivity Tomography (ERT) was first described by Lytle and Dines as a combination of traditional electrical probing (introduced by the Schlumberger brothers) and the new data inversion methods of tomography. ERT has been used in association with several geohydrological, geotechnical and geophysical methods in resolving several site-specific problems in hydrological science. Advancement in the field of computers and automation in the field of electronics has jointly resulted in the development of this geophysical innovation which has wide application in groundwater, environmental and engineering problems. In this paper, the application of ERT in association with geohydrological and other exploration methods in resolving the groundwater sustainability problem of a micro-watershed area in semi-arid hard rock terrain is presented as four independent cases. Under the project of sustainable groundwater development for rural water supply in a fluoride- endemic semi-arid region of southern India, a watershed area of 2 sqkm was selected for a pilot-scale study. Certain site-specific problems in the study area were encountered, which were attempted and understood using ERT in close association with different surface geophysical techniques and hydrological test results. Further, investigation in depth with a closed grid for better resolution of the shallow horizon was attempted in integration. In a hard rock terrain, the probability of complexities in understanding the sub-surface lithology and its corresponding hydrological parameters is higher. Hence appropriate resistivity survey configuration and suitable inversion of acquired data in congregation with other geo-scientific investigations were carried out to understand the site-specific problem. The study demonstrated four (4) independent cases showing the usefulness of the ERT method in hydrological investigations, which is economical, efficient and less time-consuming in comparison to the other exploration methods. The study concluded that geophysics plays a major role in understanding the subsurface. With scientific advancements in instrumentation, data acquisition has improved in depth and accuracy.